Schemes of suspension: motives shared in some prologues of Macedonio Fernández's Museo de la Novela de la Eterna, "El milagro secreto" by Jorge Luis Borges and La ciudad ausente by Ricardo Piglia - Torres, Martín (Ánima, 2023)
This paper analyzes shared motifs in fragments of the Argentine Macedonio Fernández-Jorge Luis Borges-Ricardo Piglia genealogy. From the literary perspective, it is intended to establish parallels between philosophy and literature to explain the idea of ​​"literary influence".
Keywords: Macedonio; Borges; literary analysis; argentinian literature; latin american literature; consciousness; liminality